Peningkatan Kualitas Laporan Keuangan : Pelatihan SAK-EMKM & Aplikasi KLEDO Pada Industri Keripik Batang Pisang Desa Cimenyan - Fia Dialysa (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
The background is financial reports have not complied with accounting standards and no digital-based financial system innovations. This will affect banking decisions to provide financing assistance and MSMEs difficulties in sustaining their business. This service aims to improve the quality of financial reports and digital-based financial innovation (fintech) then MSMEs can be highly competitive and continuously reduce banana stem waste in Cimenyan. The method used is training & mentoring so that more "bankable" to prospective borrowers from banks and a more updated financial application system is produced. The finding is the reduction of banana stem waste in Cimenyan. The implication, training program, that in the end the bank approves the application for funds. The output is partners have knowledge about financial reports that are according to standards, more practical in the fintech era. They can be highly competitive and profitable for the MSME industry on a national and international scale.